From critical theology to a critical theory of religious insight: Essays in contemporary religious thought - Lalonde, Marc Philippe; (1961-...) (Germany, 2007)
In this challenging collection of essays, Marc P. Lalonde carves out a provocative direction for contemporary religious thought. Cutting a novel path through the disciplines of critical theology, religious studies, and critical theory, this volume culminates with the groundbreaking essay `A Critical Theory of Religious Insight.` Engaging the religious as a resource for theoretical innovation, the theory advances itself as a unique form of critical theory concerned to set the religious against the normative orders of thought. This critical strategy not only bears upon the development of religious thought today but involves the extension of critical thought and theory.
Keywords: Religious thought